2005
DOI: 10.1029/2005jd006158
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of variability in continental low stratiform clouds based on observations of radar reflectivity

Abstract: [1] The variability of overcast low stratiform clouds observed over the ARM Climate Research Facility Southern Great Plains (ACRF SGP) site is analyzed, and an approach to characterizing subgrid variability based on assumed statistical distributions is evaluated. The analysis is based on a vast (>1000 hours) radar reflectivity database collected by the Millimeter-Wave Cloud Radar at ACRF SGP site. The radar data are classified into two low cloud categories and stratified by scale and the presence of precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“… Matrosov et al [2004] found a gradual deterioration of the liquid water content (L) retrieved from radar reflectivity when reflectivity threshold set for the retrieval increases, and at high reflectivity values an ambiguity exists between clouds with high L and those with drizzle. Kogan et al [2005] used −17 dBZ as the reflectivity threshold to partition their observations into non‐precipitating and precipitating clouds. They also examined the influence of varying the threshold between −20 and −15 dBZ on their results.…”
Section: Introductionmentioning
confidence: 99%
“… Matrosov et al [2004] found a gradual deterioration of the liquid water content (L) retrieved from radar reflectivity when reflectivity threshold set for the retrieval increases, and at high reflectivity values an ambiguity exists between clouds with high L and those with drizzle. Kogan et al [2005] used −17 dBZ as the reflectivity threshold to partition their observations into non‐precipitating and precipitating clouds. They also examined the influence of varying the threshold between −20 and −15 dBZ on their results.…”
Section: Introductionmentioning
confidence: 99%
“…For snowfall detection, we need to define a threshold by the CPR radar reflectivity for snowfall onset. Several investigators have so far proposed "precipitation threshold" [e.g., Haynes et al, 2009;Liu, 2008a;Sauvageot and Omar, 1987;Matrosov et al, 2004;Frisch et al, 1995;Baedi et al, 2002;Mace and Sassen, 2000;Kato et al, 2001;Kogan et al, 2005;Wang and Geerts, 2003], mostly for drizzle, with radar reflectivity generally between -20 and -10 dBZ. To be consistent with these previous studies, we define -15 dBZ as the snowfall threshold, which corresponds to about 0.01 mm h -1 snowfall rate based on the Liu [2008a] conversion formula.…”
Section: Snowfall Detection Algorithmmentioning
confidence: 99%
“…This ensures that the Doppler velocities represent the air motion and not a combination of air motion and precipitation sedimentation. A number of thresholds have been used previously to delineate clouds from precipitation (Chin et al 2000;Kato et al 2001;Kogan et al 2005;Liu et al 2008), and we chose a value of 220 dBZ to screen out most precipitation-sized particles. Only a small fraction of scans were filtered out during the 0600-1200 UTC period of interest.…”
mentioning
confidence: 99%